IDEOLOGI NASIONALISME DALAM TUTURAN UPACARA BENDERA: ANALISIS WACANA KRITIS WODAK PADA SISWA SMA - Elmirna, Nora; Rahma, Ulfa; Hermoyo, R. Panji (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Nationalism is often considered a natural characteristic, yet it is routinely produced through educational institutions to shape students' collective identity. The main focus of this research is to examine the construction of nationalist ideology in the speech of the flag ceremony at SMA Negeri 02 Bombana using Ruth Wodak's Critical Discourse Analysis model of Discourse-Historical Approach. The research stages were conducted qualitatively through the process of transcribing the speech of the ceremony instructor, field observations, and in-depth interviews to understand the institutional context. Data analysis focused on discursive strategies that include aspects of nomination, predication, argumentation, perspectivization, and the intensification and mitigation of meaning. The research findings indicate that nationalism is constructed through the framing of the inclusive identity of